The Mulino at Maccarese: IPGRI & plant genetic resources in Italy - International Plant Genetic Resources Institute (2001)
Published to mark the inauguration of IPGRI's new headquarters By the President of Italy on 3rd July 2001, The Mulino at Maccarese puts IPGRI's work in context. It contains sections on the history of IPGRI and describes the work of our host country, Italy, in conserving and using agricultural biodiversity. The area around us, Maccarese, has developed a rich agricultural heritage since being drained in the 1920s, and the booklet is illustrated with old photographs of the people and the place.